BADMINTON: HISTORY OF ORIGIN, DEVELOPMENT STAGES, TYPES, GAME RULES - Qazoqov, Sodiq Ramazonovich (International Journal of Psychosocial Rehabilitation, 2020)
badminton is one of the oldest games of human civilization. There are many legends about its origin. Ancient Greek, Japanese, Indian, and even African legends say that adults and children played badminton two thousand years ago. The ancient sport of flying feathers was known in China as early as a thousand years BC. It is called “oyabane” in Japan and is based on lifting a flywheel made of several goose feathers and dried sakura fruit on wooden rackets.